Fatigue resistance curves for single and double shear riveted joints from old portuguese metallic bridges. (February 2019) - Pedrosa, Bruno; Correia, José A.F.O.; Rebelo, Carlos; Lesiuk, Grzegorz; De Jesus, Abílio M.P.; Fernandes, António A.; Duda, M.; Calçada, Rui; Veljkovic, Milan
Abstract: The maintenance and safety of ancient bridges is a major concern of governmental authorities. In particular, the safety of old riveted bridges fabricated and placed into service at the end of the 19th century deserves particular attention. These structures are susceptible to exhibit high fatigue damage levels due to their long operational period with increasing traffic intensity associated to an original design not covering the fatigue phenomenon. This paper reviews recent fatigue behaviour investigations on single and double shear riveted joints performed by Universities of Porto (Portugal), Trás-os-Montes e Alto Douro (Portugal), and Wrocław (Poland), in particular concerning the fatigue characterization of riveted joints extracted from representative Portuguese riveted bridges, namely the Eiffel, Luiz I, Fão, Pinhão and Trezói bridges. In order to overcome the influence of scatter and establish a reliable assessment for the obtained experimental data, two statistical approaches were used: implement linearized boundaries following the recommendation in ASTM E739 standard and defining probabilistic SN fields using the Castillo & Fernández-Canteli model. This statistical analysis allows to propose design SN curves for single and double riveted joints and evaluate the applicability (safety) of using the design curves suggested in Eurocode 3 as well as design curves proposed by Taras and Greiner.